Evidence of vascular involvement in myopia: a review - Benavente-Perez, Alexandra (Frontiers in Medicine, 2023)
The benign public perception of myopia (nearsightedness) as a visual inconvenience masks the severity of its sight-threatening consequences. Myopia is a significant risk factor for posterior pole conditions such as maculopathy, choroidal neovascularization and glaucoma, all of which have a vascular component. These associations strongly suggest that myopic eyes might experience vascular alterations prior to the development of complications. Myopic eyes are out of focus because they are larger in size, which in turn affects their overall structure and function, including those of the vascular beds. By reviewing the vascular changes that characterize myopia, this review aims to provide an understanding of the gross, cellular and molecular alterations identified at the structural and functional levels with the goal to provide an understanding of the latest evidence in the field of experimental and clinical myopia vascular research. From the evidence presented, we hypothesize that the interaction between excessive myopic eye growth and vascular alterations are tipping-points for the development of sight-threatening changes.